2019
DOI: 10.1039/c9fo01092k
|View full text |Cite
|
Sign up to set email alerts
|

Natural alkaloids from lotus plumule ameliorate lipopolysaccharide-induced depression-like behavior: integrating network pharmacology and molecular mechanism evaluation

Abstract: Alkaloids from lotus plumule regulated BDNF-mediated ER stress and autophagy, subsequently attenuating neuroinflammation in LPS-stimulated BV2 microglia and LPS-induced depressive C56BL/6N mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Its main ingredient is alkaloids, which have antitumor, antibacterial, anti-inflammatory, and other biological activities (Zhang et al, 2017). Previous studies have shown that alkaloids from other plants have good antidepressant effects (Coetzee et al, 2016;Hamid et al, 2017;Jia et al, 2017;Wu et al, 2018;Arias et al, 2019;Chen et al, 2019;Khan et al, 2019), while the effect of alkaloids from S. alopecuroides on depression and gut microbes has not been investigated. In the current study, we used chronic unpredictable mild stress (CUMS) to establish a depression mouse model and assess the changes in depression-like behaviors and depression-related indicators to evaluate the beneficial effect of alkaloids on CUMS depression-like mice.…”
Section: Introductionmentioning
confidence: 99%
“…Its main ingredient is alkaloids, which have antitumor, antibacterial, anti-inflammatory, and other biological activities (Zhang et al, 2017). Previous studies have shown that alkaloids from other plants have good antidepressant effects (Coetzee et al, 2016;Hamid et al, 2017;Jia et al, 2017;Wu et al, 2018;Arias et al, 2019;Chen et al, 2019;Khan et al, 2019), while the effect of alkaloids from S. alopecuroides on depression and gut microbes has not been investigated. In the current study, we used chronic unpredictable mild stress (CUMS) to establish a depression mouse model and assess the changes in depression-like behaviors and depression-related indicators to evaluate the beneficial effect of alkaloids on CUMS depression-like mice.…”
Section: Introductionmentioning
confidence: 99%
“…in the FST and TST. [230] 4.13.12. Astragaloside IV Astragaloside IV (207, Figure 27) was an active monomer ingredient derived from Astragalus membranaceus (Fisch) Bge, which was traditionally used to treat neurodegenerative diseases.…”
Section: Higenaminementioning
confidence: 99%
“…These effects were mediated by serotonin 1A (5-HT1A) receptor [21].. In addition, Chen et al evaluated the effects of the total alkaloids (200 mg/kg) and Higenamine (50 mg/kg) on lipopolysaccharide (LPS)-induced depression by performing forced swim test (FST) and tail suspension test (TST) [22]. Then, the authors indicated molecular mechanism and identified BDNF-mediated ER stress.…”
Section: 1mentioning
confidence: 99%
“…In addition, TLA increases brain-dervived nerotrophic factor BDNF (changing BDNF expression associated with both pathological aging and psychiatric disease). Therefore, lotus plumule tea may provide a potential strategy for preventing depression [22].…”
Section: 1mentioning
confidence: 99%